Laboratory research of the stress-strain state of the drill string in the local bend of the well - Rachkevych, Ruslan; Ivasiv, Vasyl; Bui, Vasyl; Yurych Lidiіa; Rachkevych, Iryna (Technology audit and production reserves, 2018)
The object of research is the operation of the drill string in the local bend of the well. One of the most problematic aspects in this case is the establishment of its stress-strain state. This is very important information, which, in particular, is used to make decisions on the duration and possibility of operating the drill string in a given geological and technical conditions. Based on a critical literature review, physical modeling of the object of study was chosen to solve this problem. In particular, a special laboratory stand was designed, manufactured and tested, which provides: load model of the drill string axial tensile force and torque; modeling of curvilinear axes of wells with possible local excesses, based on the results of industrial inclinometry and profilometry; measurement of stresses and deformations of the model of the column and their interpretation to the values of the natural object. As a model of a drill string, a copper tube with a weighting agent was used to provide criterial similarity with a full-scale object. To measure normal stresses on a drill string model, strain gauging was used. At the same time, analog voltage values on strain gauges are digitized and transferred to a personal computer for further processing and interpretation. With the help of the proposed laboratory stand, experimental studies of the stress-strain state of a 127-mm drill string model in a local bend of well No. 10 of the Odesa deposit (Ukraine) were carried out. It has been established that the normal bending stresses that arise in this case can more than three times exceed the same values obtained without taking into account the presence of the specified curvature of the borehole axis. Thanks to the proposed experimental method, it is possible to study the deformations and stresses that occur in the drill strings during their work in wells with local axial kinks. There is no need to apply complex analytical transformations and algorithms. In addition, the model has the same physical nature as the object of study. This is an extremely weighty argument, especially in the study of complex cases of interaction between the drill string and the borehole walls.